Предмет: Алгебра,
автор: bisikalo
докажите, что выражение A+B-C тождественно равно выражению C-B-A, если A=2x-1, B=3x+1, C=5
Ответы
Автор ответа:
0
А+В-С=2х-1+3х+1-5=5х-5-=5х+5)
С-В-А=5-3х-1-2х+1=-5х+5
Как-то так..
Автор ответа:
0
А+В-С=(2х-1)+(3х+1)-5
5х=5
х=5:5
х=1
С-В-А=5-(3х+1)-(2х-1)
5-3х-1-2х+1
-5х=-5
х=-5:(-5)
х=1
Доказали
Похожие вопросы
Предмет: Русский язык,
автор: yaroslav2011
Предмет: География,
автор: Ass8a22assa22
Предмет: Алгебра,
автор: itsskatelyyn
Предмет: Биология,
автор: Натуська0009
Предмет: Литература,
автор: Apple002200